Penerapan Model Pembelajaran Think Pair Share Menggunakan Media Gambar Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas II. A Pada SDN 1 Teluk Batang Kab. Kayong Utara Propinsi Kalimantan Barat - Aisah Aisyah; Fauzi Fadliansyah; Fajar Yumanhadi Aripin (KRAKATAU (Indonesian of Multidisciplinary Journals), 2024)
This research aims to describe the implementation of Think Pair Share learning using image media so that it can increase the motivation and learning outcomes of class II.A students. The results of research on the application of the Think Pair Share learning model using image media are (1) the results of observations of the implementation of the learning model by teachers including the very good category in cycle I obtained 88% and in cycle II obtained 99%, experiencing an increase of 11%. The results of observations of the implementation of the learning model by students were in the good category from cycle I 63% and cycle II 87%, an increase of 24%. (2) increased student motivation from cycle I 85% and cycle II 87%, an increase of 5% (3) increase in student learning outcomes from cycle I 74% and cycle II 95%, an increase of 11%. (3) Response Results from 19 students gave good responses with an average response value of 85%.